The First Study on Prevalence of Bed bug in Iraq-Kurdistan region: A warning message - Khalis Ahmad Hamad Ameen (Tikrit Journal of Pure Science)
Surveys of 34 infested locations in Kurdistan region, Iraq were conducted between June, 2014 and December, 2015. Out of the 135 rooms of different locations in Kurdistan regions investigated, 56 (41.5%) were infested with bed bugs. A total of 2050 bed bugs collected, comprising 973(47.5%) males and 1077(52.5%) females, 1557 eggs were also collected. The highest number of bed bugs collected in hotel and motel 640(31.2%), whereas the lowest number observed in hospital 15(0.7%). A total of 56 infested rooms, hospital showed lowest number 2(4.9%), followed by airport 3(42.9%), whereas a highest number of rooms infestation founded in apartment 21(70%).